Comparative effects of explant sources and genotypes on microtuberization in yams (Dioscorea spp.) (2004)
Single node cuttings of two genotypes each of Dioscorea alata and D. rotundata from both plants grown in screen houses and in vitro plantlets were cultured in a tuberization medium. The screen house explants had significantly higher plantlet tuberization and primary nodal complex formation, and more tubers and primary nodal complexes per plantlet than in vitro explants, whereas in vitro explants performed better only in nodes per plantlet. It appears that in vitro tuberization is explant- , species- and genotype-dependent, the greatest variation being due to explant source. This is a first report of microtuber production from nodal explants of D. rotundata produced in a screen house.